Analysing the influence of screening ceremony strategy for the major streaming media companies: A case study of Tencent Video - Huang Yuchan; Yin Chen; Zheng Jingshi (SHS Web of Conferences, 2024)
The “screening ceremony” was established since Tencent Video embraced the “pay-on-demand-in-advance service” value-added service on top of the subscription model during the outbreak. This service’s value-added component is fairly straightforward, which causes users’ dissatisfaction and results in the termination of the value-added service. Therefore, the launch of the screening ceremony is a value-added service that better fits consumer preferences. The paper examined the current marketing strategy of Tencent Video and the illumination of the screening ceremony on the future promotion and application of major streaming video platforms to address this research gap. This investigation explored whether the “screening ceremony” could be a self-help strategy for major streaming media providers. This paper further responded to the marketing mix theory of the 4Cs and explored the four aspects of the theory and customers’ purchasing intents through the current marketing strategy of Tencent Video. Employed SWOT and qualitative analysis as strategic planning approaches. The findings of the analysis were that to increase customers’ desire to purchase, major streaming media platforms must provide customer value and connect with consumers. Meanwhile, major streaming media platforms need to provide value-added services that match the perceived value of the cost consumers pay.